Age Progression of Neuropathological Markers in the Brain of the Chilean Rodent Octodon degus, a Natural Model of Alzheimer's Disease. (10th February 2015) - Inestrosa, Nibaldo C.; Ríos, Juvenal A.; Cisternas, Pedro; Tapia‐Rojas, Cheril; Rivera, Daniela S.; Braidy, Nady; Zolezzi, Juan M.; Godoy, Juan A.; Carvajal, Francisco J.; Ardiles, Alvaro O.; Bozinovic, Francisco; Palacios, Adrián G.; et al.
Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder and the leading cause of age‐related dementia worldwide. Several models for AD have been developed to provide information regarding the initial changes that lead to degeneration. Transgenic mouse models recapitulate many, but not all, of the features of AD, most likely because of the high complexity of the pathology. In this context, the validation of a wild‐type animal model of AD that mimics the neuropathological and behavioral abnormalities is necessary. In previous studies, we have reported that the Chilean rodent O ctodon degus could represent a natural model for AD. In the present work, we further describe the age‐related neurodegeneration observed in the O . degus brain. We report some histopathological markers associated with the onset progression of AD, such as glial activation, increase in oxidative stress markers, neuronal apoptosis and the expression of the peroxisome proliferative‐activated receptor γ coactivator‐1α (PGC‐1α). With these results, we suggest that the O . degus could represent a new model for AD research and a powerful tool in the search for therapeutic strategies against AD.